1996
DOI: 10.1161/01.cir.93.12.2178
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Potential Role for the Adventitia in Vascular Lesion Formation After Balloon Overstretch Injury of Porcine Coronary Arteries

Abstract: These data suggest that adventitial myofibroblasts contribute to the process of vascular lesion formation by proliferating, synthesizing growth factors, and possibly migrating into the neointima. Increased synthesis of alpha-smooth muscle actin observed in the adventitial cells after arterial injury may constrict the injured vessel and contribute to the process of arterial remodeling and late lumen loss after angioplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
257
6
6

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 467 publications
(284 citation statements)
references
References 57 publications
13
257
6
6
Order By: Relevance
“…36,37 The adventitial also may influence atherosclerosis and vascular hypertrophy secondary to hypertension. 38 Because of the advantages that adventitial gene transfer avoids interruption of blood flow and disruption of the endothelium, as a target for site-specific vascular wall therapy, adventitial-specific gene transfer through the delivery of adenoviral vectors into the peri-arterial sheath has been demonstrated in different animal models.…”
Section: Pai-1 Prevents Aaa Hs Qian Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…36,37 The adventitial also may influence atherosclerosis and vascular hypertrophy secondary to hypertension. 38 Because of the advantages that adventitial gene transfer avoids interruption of blood flow and disruption of the endothelium, as a target for site-specific vascular wall therapy, adventitial-specific gene transfer through the delivery of adenoviral vectors into the peri-arterial sheath has been demonstrated in different animal models.…”
Section: Pai-1 Prevents Aaa Hs Qian Et Almentioning
confidence: 99%
“…38 Because of the advantages that adventitial gene transfer avoids interruption of blood flow and disruption of the endothelium, as a target for site-specific vascular wall therapy, adventitial-specific gene transfer through the delivery of adenoviral vectors into the peri-arterial sheath has been demonstrated in different animal models. 37,39,40 Adventitial delivery of vectors for gene transfer may be achieved easily in large peripheral arteries by direct application during the surgery. 38 Local overexpression of PAI-1 inhibited progression of type I aneurysms and reduced the degree of adventitial inflammation (Figures 6 and 7).…”
Section: Pai-1 Prevents Aaa Hs Qian Et Almentioning
confidence: 99%
“…Some groups have proposed that intimal VSMCs may originate from other sites than the medial layer. Adventitial fibroblasts may also migrate to the intima, differentiate into myofibroblasts and contribute to neointima formation (27,28). Moreover, several groups have shown that bone marrow-derived vascular cells with some characteristics of VSMCs accumulate in the neointima of transplant vasculopathy and in a severe vascular injury animal model (29)(30)(31).…”
Section: Early Cell Cycle Progression (G0/g1/s Phase)mentioning
confidence: 99%
“…Application of biologic or pharmacological agents to the adventitial layer of the blood vessel is appealing given that (1) the adventitial and medial layers are thought to be the source of many of the cells that populate the neointima (20,(65)(66)(67), (2) application of treatments to the perivascular region can be readily accomplished during vascular access creation and also, long after access surgery through image-guided subcutaneous injection, and (3) denudation of the endothelial layer is avoided. Biodegradable Polymer Gels.…”
Section: Perivascular Approachesmentioning
confidence: 99%